2010
DOI: 10.4049/jimmunol.0903792
|View full text |Cite
|
Sign up to set email alerts
|

Valosin-Containing Protein Cleavage by Granzyme K Accelerates an Endoplasmic Reticulum Stress Leading to Caspase-Independent Cytotoxicity of Target Tumor Cells

Abstract: Material Supplementary 2.DC1http://www.jimmunol.org/content/suppl/2010/09/27/jimmunol.090379References http://www.jimmunol.org/content/185/9/5348.full#ref-list-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 42 publications
0
31
2
Order By: Relevance
“…17 Finally, (Hu)gzmK was shown to cleave a vasolin-containing protein resulting in accelerated endoplasmic reticulum stress and caspase-independent cytotoxicity of tumor cells. 18 In marked contrast, this study demonstrates that ex vivo-derived LCMV-immune Tc cells which are positive for gzmK but negative for gzmA and gzmB expressed only marginal proapoptotic/cytotoxic activities, especially when measured by sensitive markers that assess plasma membrane and mitochondrial integrity, as well as by a target cell-survival assay. This finding agrees with reports showing that LCMVand ectromelia-immune gzmAxB À/À Tc cells show marginal pro-apoptotic activity.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…17 Finally, (Hu)gzmK was shown to cleave a vasolin-containing protein resulting in accelerated endoplasmic reticulum stress and caspase-independent cytotoxicity of tumor cells. 18 In marked contrast, this study demonstrates that ex vivo-derived LCMV-immune Tc cells which are positive for gzmK but negative for gzmA and gzmB expressed only marginal proapoptotic/cytotoxic activities, especially when measured by sensitive markers that assess plasma membrane and mitochondrial integrity, as well as by a target cell-survival assay. This finding agrees with reports showing that LCMVand ectromelia-immune gzmAxB À/À Tc cells show marginal pro-apoptotic activity.…”
Section: Discussioncontrasting
confidence: 60%
“…[14][15][16] (Hu)gzmK may also cleave the tumor suppressor, p53, thus sensitizing tumor cells for apoptosis induction 17 and may process a vasolin-containing protein, thus contributing to endoplasmic reticulum stress and caspase-independent cytotoxicity. 18 Compared with the proposed cytotoxic role for gzmK, the protease has been found by immunoassays 19 to be elevated in the plasma of patients with sepsis 20 and in the bronchoalveolar fluid of patients with asthma and viral pneumonias, 21 suggesting that gzmK may have additional biological functions.…”
mentioning
confidence: 99%
“…The inhibitor of cytotoxic granule pathway concanamycin A (CMA) could inhibit but not block LAK cellinduced cytolysis, which is in agreement with our previous reports. 25,26 These data indicate that the extrinsic death pathway is involved in LAK cell-mediated cytolysis in addition to a major granule pathway. Figure 5A).…”
Section: Resultsmentioning
confidence: 85%
“…12 GzmK also cleaves the valosincontaining protein (VCP) to destroy the ER-associated degradation (ERAD) pathway, resulting in an ER stress of the target cell. 13 We also found that GzmK proteolyzes the tumor suppressor p53 to generate three pro-apoptotic segments that potentially increase elimination of target tumor cells. 14 In this study, we showed that GzmK can cleave the importin a1/b dimer and disrupt transportation of viral NP to the nucleus, resulting in elimination of influenza virus in vivo.…”
mentioning
confidence: 69%
“…We have previously showed that the GzmK inhibitor Ac-YRFK-CMK can specifically block enzymatic activity of GzmK. 13 Mice were then intranasally infected with the Flu A/WSN/33 (H1N1) (10 2 PFU/mouse) virus. KI-pretreated mice showed significantly higher viral loads in their lungs than did PBS controls at both 3 days and 6 days post infection (p.i.)…”
Section: Gzmk Blockade Aggravates Influenza Virus Infectionmentioning
confidence: 99%